THE POSITION OF STATE RESPONSIBILITY FOR ENVIRONMENTAL POLLUTION BY CORPORATE : The Legal Studies of Implementation Paradigm Polluter Pay Principle in Environmental Law Enforcement in Indonesia - Priyanta, Maret (Tadulako Law Review, 2016)
The development activities is one of the government's efforts in order to realize a fairness and prosperous for the society. The natural resources management through the business activities carried out by the corporation, became one of the important factors in the success of national development. One of the impacts of development activities on the environment is the environmental pollution because of the utilization of natural resources. The pollution has caused a decrease in the quality of human life and other living creatures. Differences paradigm or way people view the polluter pays principle and the position of the responsibility of States to discredit the corporation still there is a difference of view and understanding. It is see from the practice of application of the Social and Environmental Responsibility (TJSL), which seems to have been removing corporate responsibility and involvement allocationof State budget revenue and expenditure of the State to penangulangan pollution, which performed by the corporation. This has led to uncertainty in the law enforcement environment in Indonesia. This study aimed to describe the problem from the legal aspect and theory in relation to the position of state responsibility and corporate environmental pollution in the environmental legal system. This study uses normative juridical approach, through the method of approach to legislation, the conceptual approach, and an analytical approach. The scope of this normative juridical research includes the study of the principles and theory of law. Paradigm reform of the principles of pollution should be change or reform based on theory of law, whereby the position and extent of responsibility of states and corporations definitely be regulated in the Indonesia environmental legal system.